The Influence of the Russian and Ukraine Conflict on Indonesian Economic Development Review of Theotonio Dos Santos Theory (Dependency Theory) - Rahmat Sutiyono; Muhammad Husin Ali; Akhmad Saripudin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
February 24, 2022 Russia begins its invasion of Ukraine. The situation and condition of countries in the world that have just started to recover from being hit by COVID-19, are actually made to worry again due to the Russian invasion of Ukraine. The implications that are felt are quite painful, especially in the economic field. The world economic situation will weaken in line with rising commodity prices, especially in the economic and food sectors due to the conflict. Indonesia is a country that is active in trade transactions both export and import activities will certainly feel the impact of this conflict. In this study, the author places the formulation of the problem, namely how the influence of the Russian-Ukrainian conflict on Indonesia's economic development in terms of dependency theory. Then, this research uses the type of research that is carried out by normative research and uses the type of theoretical research (theoretical research). In the conflict between Russia and Ukraine, Indonesia was quite firm in stating its position as a "free and active" country, which is an advantage for Indonesia to be able to continue to carry out investment activities and export transactions with other countries, including countries involved in the conflict. so that the Indonesian economy continues to grow even in unsafe conditions and situations. But on the other hand, it must be remembered that Indonesia is a developing country that still carries the status of a country that depends on developed countries. So, when the economies of developed countries weaken such as the United States, China, and Russia for example, then Indonesia will feel the same way, the Indonesian economy will also be affected by this. This is the description of the dependency theory explanation put forward by Theotonio Dos Santos.